Project and maintainability in the era of Industry 4.0 - Massimo Lauria; Maria Azzalin (Techne, 2019)
The paper deals with the many issues related to the relationship between project and maintainability in light of the opportunities offered by Industry 4.0 referred to scientific advances and international and national regulatory context. As for industrial products, building maintainability is a design requirement and requires tools, procedures and programming skills. Not new issues, different the connoting characters. Today, Lean Construction and ICT technologies are synergetic methodologies and tools aimed at improving the “predictability” of design. They represent some of the cornerstones of an innovative approach, capable of projecting the construction sector into the era of the fourth revolution and, even more, the design practices from which descend the choices and strategies for managing the life cycle and therefore the characteristics of efficiency and sustainability. In this context, project and maintainability find a re-reading and updating, not only with reference to their operational capacity, but also mainly considering renewed human-centered approaches.